Alimentação saudável: educando e cuidando da infância na educação infantil - Giaretta, Mariele (2020)
This article presents a review of the literature on the topic of healthy eating in early childhood education. The introduction of healthy food for the integral development of the child in this teaching phase was the general objective of this investigation, since, at this stage, food preferences are created. Thus, when it becomes opportune to learn to choose the healthiest foods, the risk, throughout life, of individuals developing heart disease, diabetes, immune deficiencies, obesity, among others, becomes reduced. It is understood, therefore, that food education and good eating practices favor the knowledge of the student and enable quality of life. The actions of educating, caring and building knowledge about the importance of eating properly influence the promotion of good eating habits continuously.